Multivariate Analysis of the Attributes of a Central Attacking Midfielder - Nwokike, Innocent Chukwudozie; Ngozie, Erumaka Ephraim; Chrysogonus, Nwaigwe; Chuks, Obi Martin (Yayasan Insan Literasi Cendekia (INLIC) Indonesia, 2024)
Central attacking midfielders are one of the most vital squad members because of their decisive contributions to the team in the field of play. With teams now acquiring some talented players for as much as 103 million euros, it has become more important than ever to critically investigate the attributes of a central attacking midfielder. This study is designed to investigate the correlation between attributes (variables) such as crossing, finishing, short passing, volleys, dribbling, curve, long passing, ball control, acceleration, sprint speed, agility, stamina, vision, penalties, and composure, using multivariate analysis techniques. The study used canonical correlation analysis (CCA) to analyze these correlations. The study produced three statistically significant canonical functions with canonical correlations of , , and , respectively. The study also showed that canonical function 1 showed more significance (Wilks's and ). A principal component analysis (PCA) was conducted to determine the most important variables for a central attacking midfielder. The PCA generated four components. The first component showed itself to be optimal, with variables such as short passing, long passing, vision, composure, and ball control highlighted as the most relevant attributes of a central attacking midfielder. The study also developed a dynamical system that can be analyzed to understand the efficiency of the central attacking midfielder with respect to the given variables and parameters.